Bacterial Communities Are More Sensitive to Water Addition Than Fungal Communities Due to Higher Soil K and Na in a Degraded Karst Ecosystem of Southwestern China - Umair, Muhammad; Sun, Ningxiao; Du, Hongmei; Hui, Nan; Altaf, Muhammad; Du, Baoming; Yin, Shan; Liu, Chunjiang (Frontiers in Microbiology, 2020)
Precipitation is predicted to become more intense in Southern China in the context of climate change, however, the responses of microbial communities to variations in soil moisture have not been well documented for karst areas. The climate is typically in a subtropical monsoon category with two different seasons: a dry season (December-May), and a wet season (June-November). Based on a RCBD design, a water addition experiment (0%, +20%, +40%, and +60% relative to local precipitation) was established in April 2017, with five replicates, in a degraded grass-shrub community. Sampling was performed in May and at the end of August of 2017. The total DNA of the soil samples was analyzed through 16S rRNA apmlicon by Illumina Miseq. Subsequent to the addition of water during both seasons, the concentrations of non-metal elements (C, H, N, S, and P, except for Si) in the soil remained relatively stable; however, metal elements (K, Na, Fe, and Mg, along with Si) increased significantly, whereas Zn and Ca decreased. During the dry season, fungal and bacterial communities were significantly distinct from those during the wet season along the PC axis-1 (p < 0.001). Water addition did not alter the compositions of bacterial or fungal communities during the dry season. However, during the wet season, water addition altered the compositions of bacterial rather than fungal community based on principal component analysis. At the phylum level, the relative abundance of Actinobacteria increased with water addition had a significantly positive correlation with K+ (r2 = 0.70, p < 0.001) and Na+ (r2 = 0.36, p < 0.01) contents, whereas that of Acidobacteria, Planctomycetes, and Verrucomicrobia decreased and showed negative correlation with soil K and Na content, and no changes were observed for the fungal phyla. This suggests that the karst bacterial communities can be influenced by the addition of water during the wet season likely linked to changes in soil K and Na contents. These findings implied that increased rainfall might alter the elemental compositions of karst soils, and bacterial communities are likely to be more sensitive to variations in soil moisture in contrast to their fungal counterparts.